THE ACCESSIBILTY OF DISABLED PEOPLE IN ADAPTED SPORTS AND ACTIVITIES (Fiep Bulletin - online, 2013)
This article takes part from a survey conducted with a group on a regular practitioner of sport adapter, from an ethnographic perspective, discussing public policies on access for disabled people in sports and activities. We evaluated the type of sports activity offered, what are the benefits, how they happen and how to access those people in that institution. This research sought to identify the different modes of perception of the work of the group that offers adapted sports activities. The research also addresses the issue of accessibility in public policy perspective and also from the perspective of internal institutions.